THE EFFECT OF TRAINING AND DEVELOPMENT, MOTIVATION, AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. HASJRAT ABADI TENDEAN - Areros, Kartika L.; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2018)
Abstract: Employeeâ€™s performance can be influence by some other factors such as training and development, motivation, and leadership style. Itâ€™s a part of performance management system in the workplace. PT. Hasjrat Abadi is known as one of the automotive company in Indonesia. PT. Hasjrat Abadi is a network of sales services, maintenance, repair, supply of spare parts and accessories Toyota region of eastern Indonesia and also an exclusive distributor of Toyota and Yamaha vehicles in eleven of the leading province, region of Central & Eastern part of Indonesia. This research aims to know the influence of training and development, motivation, and leadership style on employee performance at PT. Hajsrat Abadi Tendean. The sample of this research is 98 respondents which are the total employee at PT. Hasjat Abadi Tendean. This research used multiple linear regression analysis. The result shows that training and development, motivation, and leadership style are significantly and positively influence the employee performance, simultaneously and partially. Hasjrat Abadi Tendean Manado should keep their proficiency of the skill and ability training, so their employee can give an efficient work that can increase the company performance in all sectors.Â Keywords: employee performance, training and development, motivation, leadership style